Security Camera Implementation System on Smart Home Using Web-Based Frame Difference Methods - Mochamad Faiz Irawanto; Azam Muzakhim Imammuddien; Rieke Adriati Wijayanti (Politeknik Negeri Malang, 2023)
The development of technology in the field of security has a big impact on people's lives throughout the world. The security is threatened when there is a burglary in the neighborhood. One of the applications of image processing is the frame difference method, which used comparison of the captured image frame circuit according to time order. Frame difference algorithm applied to grayscale image computing using ESP32-CAM cameras for security cameras. This research was developed with a system that can monitor objects detected in real-time by streaming using a website. The ESP32-CAM camera and the PC have a packet loss value of 4.29% and an average delay of 0.3 seconds so that the images captured by the camera can be well received by the PC. The frame difference method with moving objects is used and detected well during the day due to solar lighting, but at night only depends on luminous objects. This method has the disadvantage that when moving objects inhabit the same field of view, the system will define it as movement so that the frame difference method is not adaptive from changes in the captured area.